Implementasi Transformasi Kelembagaan Pendidikan Agama Islam Masa Daulah Di Era Kontemporer - Auliya, Muhamad Fahmi Ridho; Sutrisno, Sutrisno; Hariyadi, Rahmad; Rofiq, Muhamad (Institut Kariman Wirayudha Sumenep, 2024)
This research discusses the transformation of Islamic education during the Umayah period in the contemporary era. With a literature-based qualitative approach, this research reviews the history of the establishment of Daulah Umayah, the role of Islamic thinkers in the development of Islamic education, and the implementation steps of the transformation of Islamic education institutions in the contemporary era. Data were obtained from analyzing relevant scientific literature. The results of this study are expected to provide a deeper insight into changes in Islamic education and its adaptation to social and technological changes.